The Notary Position in The System of Corporation and Legal Contract Industry in Bangladesh - Misty, Mousume Akter (Jurnal Daulat Hukum, 2024)
Notaries play a vital role in preserving the integrity of legal transactions and upholding justice in the domain of legal systems. Examining the function of notaries and their adherence to ethical codes in Bangladesh is crucial as the nation develops and negotiates difficult legal issues. In order to clarify this important facet of the legal system, a thesis proposal titled "The Function of a Notary Position in the Legal Contract in the Bangladesh Industry" was created. This research seeks to provide important insights that can improve the effectiveness, transparency, and reliability of legal affairs in Bangladesh by exploring the complexities of notarial practices and the ethical principles that guide their responsibilities and moral conduct in the nation's legal system. The goal of the thesis, "The Function of a Notary Position in the Legal Contract in the Bangladesh Industry," is to investigate and evaluate notaries' importance and function in relation to legal contracts in the Bangladeshi market. The thesis examines several notary functions, including the legal framework that governs them, the roles and responsibilities of notaries, their impact on the enforceability and validity of contracts, and the overall effectiveness of notary services in Bangladesh, with the goal of ensuring legal compliance and protecting the interests of contracting parties. In addition, the thesis probably looks at how notary services have changed historically in Bangladesh, any laws or rules governing their practice, and any shortcomings or potential improvements to the current setup. Through thorough research, analysis, and possibly case studies or empirical data, the thesis may attempt to further our understanding of the role notaries play in facilitating contractual transactions and enhancing the security and legal certainty of business operations in the Bangladeshi industry.